2023
DOI: 10.3389/fimmu.2023.1106459
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune-inflammation index is associated with aneurysmal wall enhancement in unruptured intracranial fusiform aneurysms

Abstract: IntroductionInflammation plays a key role in the progression of intracranial aneurysms. Aneurysmal wall enhancement (AWE) correlates well with inflammatory processes in the aneurysmal wall. Understanding the potential associations between blood inflammatory indices and AWE may aid in the further understanding of intracranial aneurysm pathophysiology.MethodsWe retrospectively reviewed 122 patients with intracranial fusiform aneurysms (IFAs) who underwent both high-resolution magnetic resonance imaging and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Inflammatory processes play a significant role in the development of IA 30,31 . Several research exploring the association between chronic inflammation and IAs suggested that persistent disruption of the peripheral immune environment may induce the formation of IAs through inflammatory cascades 32–35 . In the present, it was observed that PBMCs, as a crucial component of the peripheral immune environment, exhibited metabolic dysregulation associated with numerous diseases.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Inflammatory processes play a significant role in the development of IA 30,31 . Several research exploring the association between chronic inflammation and IAs suggested that persistent disruption of the peripheral immune environment may induce the formation of IAs through inflammatory cascades 32–35 . In the present, it was observed that PBMCs, as a crucial component of the peripheral immune environment, exhibited metabolic dysregulation associated with numerous diseases.…”
Section: Discussionmentioning
confidence: 51%
“… 30 , 31 Several research exploring the association between chronic inflammation and IAs suggested that persistent disruption of the peripheral immune environment may induce the formation of IAs through inflammatory cascades. 32 , 33 , 34 , 35 In the present, it was observed that PBMCs, as a crucial component of the peripheral immune environment, exhibited metabolic dysregulation associated with numerous diseases. In our study, metabolic profiling of PBMCs revealed distinct metabolic characteristics among different subsets.…”
Section: Discussionmentioning
confidence: 72%
“…Man Xu et al reported in a retrospective cohort study of 13,929 middle‐aged and elderly people that SII can be used as a useful indicator to clarify the interaction between thrombocytosis and immune inflammation in the occurrence and development of cerebral vascular disease in middle‐aged and elderly people 34 . Other studies also reported the potential role of SII in cardiocerebral vascular disease 35–37 . A higher SII has also been associated with an increased risk of POCD, 38 rheumatoid arthritis, 39 and postoperative pulmonary complications 40 …”
Section: Discussionmentioning
confidence: 99%
“… 34 Other studies also reported the potential role of SII in cardiocerebral vascular disease. 35 , 36 , 37 A higher SII has also been associated with an increased risk of POCD, 38 rheumatoid arthritis, 39 and postoperative pulmonary complications. 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation